Vulnerability to cardiac arrest in patients with ST elevation myocardial infarction: Is it time or patient dependent? Results from a nationwide observational study. Issue 4 (November 2020) - Salah, Mahadi; Gevaert, Sofie; Coussement, Patrick; Beauloye, Christophe; Sinnaeve, Peter R; Convens, Carl; De Raedt, Herbert; Dens, Jo; Pourbaix, Suzanne; Saenen, Johan; Claeys, Marc J
Aim: Cardiac arrest is a common complication of ST elevation myocardial infarction and is associated with high mortality. We evaluated whether vulnerability to cardiac arrest follows a circadian rhythm and whether it is related to specific patient characteristics. Methods: A total of 24, 164 ST elevation myocardial infarction patients who were admitted to 60 Belgian hospitals between 2008–2017 were analysed. The proportion of patients with cardiac arrest before initiation of reperfusion therapy was calculated for different time periods (hour of the day, months, seasons) and related to patient characteristics using stepwise logistic regression analysis. Results: Cardiac arrest occurred in 10.8% of the ST elevation myocardial infarction patients at a median of 65 min (interquartile range 33–138 min) after onset of pain. ST elevation myocardial infarction patients with cardiac arrest showed a biphasic pattern with one peak in the morning and one peak in the late afternoon. Multivariate analysis identified the following independent factors associated with cardiac arrest: cardiogenic shock (odds ratio=28), left bundle branch block (odds ratio=3.7), short (<180 min) ischaemic period (odds ratio=2.2), post-meridiem daytime presentation (odds ratio=1.4), anterior infarction (odds ratio=1.3). Overall in-hospital mortality was 30% for cardiac arrest patients versus 3.7% for non-cardiac arrest patients ( p <0.0001). Conclusion: In the present study population, cardiac arrest in ST elevation myocardial infarction showed an atypical circadian rhythm with not only a morning peak but also a second peak in the late afternoon, suggesting that cardiac arrest and ST elevation myocardial infarction triggers are, at least partially, different. In addition, specific patient characteristics, such as short ischaemic period, cardiogenic shock and left bundle branch block, increase the vulnerability to cardiac arrest.